Development Of Trainer Learning Media Kit Solar Cell Public Road Lighting System in Electrical Light Installation - Rian, Rian Pratama; Sukardjo, Moch; Muksin (Kirana Publisher (KNPub), 2024)
This research studies to develop instructors of electric lighting installation instructor media learns the feasibility of learning media for electrical installations trainers, learns the feasibility of worksheets for electric lighting installation learning media, and studies the effectiveness of learning media for electrical installations. Development (R&D) using the ADDIE model (analysis, design, development, implementation, evaluation). By citing: (1) Analyzing (containing: analysis of design and needs, analysis of learning, analysis of students and obtaining difficulties there is no learning media for electrical installations), (2) Design (includes: large component trainers of electric contents, electricity, and trainer design), (3) Development (including making learning media broadcast by media experts and material experts), (4) Implementation (including conducted in class XI TL 2 SMK Negeri 2 Kota Serang starting with a pretest to find out where to find students IPL and then apply the learning media that has been developed) and (5) Evaluation (provided: done by providing a post-test to determine the effectiveness of the media that has been made). Based on the results of research that has been done, obtained data on the feasibility of instructional media with an average score of 82 categories